Black Phosphorus Cytotoxicity Assessments Pitfalls: Advantages and Disadvantages of Metabolic and Morphological Assays - Fojtů, Michaela; Balvan, Jan; Raudenská, Martina; Vičar, Tomáš; Bouša, Daniel; Sofer, Zdeněk; Masařík, Michal; Pumera, Martin (Chemistry (Weinheim an der Bergstrasse, Germany), 2019)
Black phosphorus (BP) belongs to a group of 2D nanomaterials and nowadays attracts constantly increasing attention. Parallel to the growing utilization of BP nanomaterial increase also the requirements for the thorough comprehension of its potential impact on human and animal health. The aim of this study was to compare and discuss five assays commonly used for the cytotoxicity assessments of nanomaterials with a special focus on BP nanoparticles. A comprehensive survey of factors and pitfalls is provided that should be accounted for when assessing their toxicity and pointed to their inconsistency. BP might introduce various levels of interference during toxicity assessments depending on its concentration applied. More importantly, the BP toxicity evaluation was found to be influenced by the nature of assay chosen. These are based on different principles and do not have to assess all the cellular events equally. A commercial assay based on the measurement of protease activity was identified to be the most suitable for the BP toxicity assessment. Further, the benefit of time-lapse quantitative phase imaging for nanomaterial toxicity evaluation was highlighted. Unlike the conventional assessments it provides real-time analysis of the processes accompanying BP administration and enables to understand them deeper and in the context.
Keywords: mikroskopie atomárních sil; interference; holographic microscopy; cytotoxicity; black phosphorus; Cell Line, Tumor; fosfor; Nanoparticles; Time-Lapse Imaging; lidé; 2D nanomaterials; nanočástice; X-Ray Diffraction; Phosphorus; difrakce rentgenového záření; časosběrné zobrazování; nanoparticles; Microscopy, Atomic Force; Cell Survival; viability; viabilita buněk; nádorové buněčné linie; Humans